Dos Nuevas Especies de Hechtia (Bromeliaceae) de México - Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa; Ramírez-Morillo, Ivón; Martínez-Correa, Nancy (Instituto de Ecología, A.C., 2007)
Hechtia nuusaviorum and H. perotensis are described and illustrated. The former is a species endemic to Oaxaca and the second is known from Veracruz and Puebla states, from the region known as Valle de Perote.